(untitled) (REMUNOM, 2024)
The inappropriate use of antimicrobials, including self-medication, is a growing concern in clinical practice, contributing to bacterial resistance and the progression to more severe clinical conditions. This study, through an integrative literature review, investigated the challenges and strategies related to the use of antimicrobials, with a focus on self-medication and bacterial resistance. The analysis of ten studies published between 2020 and 2024 revealed the prevalence of self-medication, influenced by socioeconomic and cultural factors, and the crucial role of pharmacists in patient education. Antimicrobial resistance is a recurring problem, emphasizing the importance of pharmaceutical care and Antimicrobial Stewardship Programs (ASP) in promoting the rational use of medications. Studies have shown the positive impact of ASPs in reducing antimicrobial consumption and highlighted the need to integrate antimicrobial stewardship concepts into the medical curriculum. Patient education and improved prescribing practices, including stricter guidelines and regular audits, are essential strategies to combat the inappropriate use of antimicrobials. A multifaceted approach involving education, antimicrobial stewardship, and proactive action by healthcare professionals is critical to ensuring treatment effectiveness, patient safety, and the sustainability of healthcare systems in combating antimicrobial resistance.